MABBAKANG TRADITION (Case Study of Local Cultural Values in the Pange Community, Mattappawalie Village, Barru Regency) - Mastura, Emi; Akhiruddin; Amir, Arfenti; Sriwahyuni (CV. Eureka Murakabi Abadi, 2024)
This study aimed to determine the public perception of the mabbakang tradition in Pange, Mattappawalie Village, Barru Regency. This type of research is a qualitative case study type using purposive sampling to determine research informants. The techniques in data collection are observation, interviews, and documentation. With data analysis techniques through data collection, data reduction, data presentation and concluding. The results of this study are the perception of the Pange community regarding the mabbakang tradition, namely (a) the mabbakang tradition as a tradition of giving honey or maccani; (b) the mabbakang tradition as a tradition of warding off disaster.